Binary stress induces an increase in indole alkaloid biosynthesis in Catharanthus roseus - Zhu, Wei; Yang, Bingxian; Komatsu, Setsuko; Lu, Xiaoping; Li, Ximin; Tian, Jingkui (Frontiers in Plant Science, 2015)
Catharanthus roseus is an important medicinal plant, which produces a variety of indole alkaloids of significant pharmaceutical relevance. In the present study, we aimed to investigate the potential stress-induced increase of indole alkaloid biosynthesis in C. roseus using proteomic technique. The contents of the detectable alkaloids ajmalicine, vindoline, catharanthine, and strictosidine in C. roseus were significantly increased under binary stress. Proteomic analysis revealed that the abundance of proteins related to tricarboxylic acid cycle and cell wall was largely increased; while, that of proteins related to tetrapyrrole synthesis and photosynthesis was decreased. Of note, 10-hydroxygeraniol oxidoreductase, which is involved in the biosynthesis of indole alkaloid was two-fold more abundant in treated group compared to that in control. In addition, mRNA expression levels of genes involved in the indole alkaloid biosynthetic pathway indicated an up-regulation in their transcription in C. roseus under UV-B irradiation. These results suggest that binary stress might negatively affect the process of photosynthesis in C. roseus. In addition, the induction of alkaloid biosynthesis appears to be responsive to binary stress.